Konstruksi Pengetahuan Siswa SD Tentang Gerhana Melalui Integrasi Sains dan Kearifan Lokal : Studi Kasus Bancakan Gerhono di Desa Boja Kecamatan Tersono Kabupaten Batang - Novita Barokah (Jurnal Bintang Pendidikan Indonesia, 2025)
This study aims to construct elementary school students understanding of the eclipse phenomenon through the integration of science and local wisdom. This case study explores the use of the Bancakan Gerhono tradition as a learning method to improve students conceptual understanding of the eclipse, as well as how this approach can strengthen culture based learning. This study uses a qualitative approach with a case study method. The subjects of the study consisted of 6th grade elementary school students and science teachers at SDN Boja 01. Data validity techniques were carried out through triangulation of sources, methods, researchers, and theories. Data were analyzed using an interactive model from Miles, Huberman, and Saldana (2014) which includes the stages of data reduction, data presentation, and drawing conclusions/verification. The results of the study showed that the integration of the Bancakan Gerhono tradition in science learning significantly improved students understanding of eclipses. Students were able to relate scientific concepts to their cultural context, making learning more meaningful and relevant. The acceptance of the integration of local wisdom in learning was very positive, both from students and teachers. This approach was also proven to be effective in increasing student engagement and strengthening their conceptual understanding. The implications of this study emphasize the importance of integrating local wisdom into the science curriculum to create holistic and contextual learning. this study also recommends further development regarding the application of local tradition sin various disciplines in elementary school.